Invisible citizens: how marginalized Ghanaian LGBT+ citizens shape their stories on Instagram - Addison, Sheilla, author; Arthur, Tori, advisor; Humphrey, Mike, committee member; Attai, Nikoli, committee member (Colorado State University. Libraries, 2024)
In Ghana, like most African countries, LGBT+ members are relegated to the background and generally live in fear of persecution. The media has played an instrumental role in framing the discourses surrounding queerness, leading to exclusion, marginalization, and moral panic in the country. Currently, the emergence and active use of social media have afforded many Ghanaians a platform to engage and express harmful opinions that are implicit and explicit queerphobia. In a similar vein, queer activists and some LGBT+ individuals have appropriated social media platforms, including Instagram, as a powerful alternative platform to redefine negative stereotypes, challenge the narratives around marginalized LGBT+ citizens and provide an alternative way of viewing their worlds. Using defensive digital alchemy as its theoretical framework, this thesis employs Critical Technocultural Discourse Analysis to assess @lgbtrightsghana's defensive digital alchemy in Instagram to fight against the marginalization of sexual identities in the face of Ghana's anti-LGBT+ Bill. The findings suggest that @lgbtrightsghana's defensive digital alchemy challenges master narratives, redefines negative stereotypes, and provides alternate views of queer Ghanaians.
Keywords: CTDA; Instagram; master and counter narratives; defensive digital alchemy; Anti-LGBT+ Bill; LGBT+